Problematika Sosial dan Keagamaan Dalam Keluarga Beda Agama Di desa Sendangmulyo Kabupaten Kulon Progo Yogyakarta - Novita Misika Putri, Tantan Hermansah, Kiky Rizky (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
Different religious marriages are an interesting social phenomenon to study. This study purposed to explain the social and religious problems in the family of different religions. It used a qualitative research approach. Data collection techniques used observation, interviews, and documentation. The findings revealed that basically, a good marriage to create harmony, happiness, and prosperity in the family is a marriage between two people who have the same aqidah. Conversely, marriage between two different beliefs or different religious marriages strongly triggers conflicts such as less harmonious, happiness, and prosperous. In different religious families, there are social problems and religious problems. Social problems that arise include an unfavorable interaction between husband, wife, children, relatives of husband, and relatives of wife. While religious problems occur in the implementation of ritual worship from the side of husband, wife, and children as well as the selection of religious children, child religious development, and application of inheritance rights.